Carbapenem resistant Escherichia coli and Klebsiella pneumoniae in community wastewaters of Dhaka, Bangladesh - Shafi, Sazid Al (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.